STUDIES ON THE CHARACTERISTICS OF SPECTRAL SOLAR IRRADIATION IN THE TROPICS: A CASE STUDY OF MALAYSIA - Said Fhazli (LPPM Universitas Muhammadiyah Riau, 2011)
A Multifilter Rotating Shadowband Radiometer has been used to monitor the directly transmitted solar irradiance at six wavelength regions (413.9 nm, 494.6 nm, 612.7 nm, 670.8 nm, 868.0 nm and 939.1 nm) for three clear stable days at Bangi. The primary objective of this study is to determine the aerosol optical depth (AOD), total column ozone (TCO) and precipitable watercontent (PWC). The result shows that the maximum optical depth of aerosol at the shorter wavelength, especially on 24th February 2002 with mean value of 0.254 (24th February 2002), 0.095 (25th February 2002), and 0.072 (26th February 2002) while the ozone optical depth shows the mean value 0.0153 on 24th February 2002, 0.0174 on 25th February 2002 and 0.0175 on 26thFebruary 2002 with the avarage absorption coefficient (a), 0.2 (24th and 26th February 2002) and 0.1 (25th February 2002). The mean value of water vapor content shows that  = 0.356 cmand k = 0.301 cm for wavelength 939.1 nm. From the aerosol optical depth, it shows the existence of smoke type of aerosol on February, 24th to 25th 2002 with Ångström coefficient, , is 1.534 and 1.5513, respectively, and sea water vapor is 0.9889 on 26th February 2002. From the Ångström coefficient, it shows that atmosphere layer of Bangi at that moment is similar to U.S. Standard Atmosphere, with maximum spectral irradiance on black body temperature is 5860 oK.